Anthropometric Obesity Indices were Stronger than CT-Based Indices in Associations with Carotid Intima-Media Thickness in Japanese Men - Liu, Yuyan (J Atheroscler Thromb, 2019)
Aim: Computed tomography (CT) can directly provide information on body compositions and distributions, compared to anthropometric indices. It has been shown that various obesity indices are associated with carotid intima-media thickness (IMT). However, whether CT-based obesity indices are stronger than anthropometric indices in association with atherosclerosis remains to be determined in a general population. Methods: We cross-sectionally assessed carotid IMT using ultrasound in 944 community-dwelling Japanese men free of stroke and myocardial infarction. CT image at the L4-L5 level was obtained to compute areas of visceral adipose tissue (VAT) and subcutaneous adipose tissue (SAT). Anthropometric measures assessed included body mass index (BMI), waist circumference, and waist-to-hip ratio. Using multivariable linear regression, slopes of IMT per 20(th) to 80(th) percentile of each index were compared. We also compared the slope of index with simultaneous adjustment for BMI in the same model. Results: Areas of VAT and SAT were positively associated with IMT, but not stronger than those of anthropometric indices in point estimates. Among all obesity indices, BMI was strongest in association with IMT after adjusting for age and lifestyle factors or further adjusting for metabolic factors. In simultaneous adjustment models, BMI, but not CT-based indices, remained significant and showed the strongest association. Conclusions: In community-dwelling Japanese men, anthropometric obesity indices, BMI in particular, were more strongly associated with carotid atherosclerosis than CT-based obesity indices. The association of general obesity with carotid atherosclerosis was strong and adding CT-based obesity measure did not considerably influence in the association.